THE EFFICACY OF INNOVATIVE METHODS IN REDUCING SPEECH ANXIETY IN ENGLISH LANGUAGE CLASSROOMS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Foreign Language Speaking Anxiety (FLSA) remains a significant psychological barrier for students aiming for communicative competence. Despite possessing adequate grammatical knowledge, many learners experience "freezing" during oral production. This article investigates the efficacy of innovative pedagogical interventions—including Gamification, Virtual Reality (VR) simulations, and Task-Based Language Teaching (TBLT)—in mitigating speech anxiety. By analyzing the intersection of the Affective Filter Hypothesis and modern educational technology, the study argues that low-stakes, immersive environments are essential for fostering oral fluency. The paper concludes with practical recommendations for educators to create "anxiety-free" zones in higher education.